Universal cosmologies - Paul Marconnet; Dimitrios Tsimpis (Journal of High Energy Physics)
Abstract Universal cosmologies are exact solutions of 10d type IIA supergravity containing a 4d Friedmann-Lemaître-Robertson-Walker factor, that can also be repackaged as solutions of 4d models, i.e. as 4d consistent truncations. We extend the dynamical system analysis of universal cosmologies, beyond the case of a single exponential potential. For an open universe (negative 3d spatial curvature), these models generally possess many desirable features: parametric control of e-folds, late-time acceleration from potentials with steep exponentials (i.e. in accordance with swampland bounds), small string-loop and α ′-corrections, scale separation and/or absence of decompactification.